Predicting Psychotic-Like Experiences during Sensory Deprivation - Daniel, Christina (Biomed Res Int, 2015)
Aims. This study aimed to establish the contribution of hallucination proneness, anxiety, suggestibility, and fantasy proneness to psychotic-like experiences (PLEs) reported during brief sensory deprivation. Method. Twenty-four high and 22 low hallucination-prone participants reported on PLEs occurring during brief sensory deprivation and at baseline. State/trait anxiety, suggestibility, and fantasy proneness were also measured. Results. Both groups experienced a significant increase in PLEs in sensory deprivation. The high hallucination prone group reported more PLEs both at baseline and in sensory deprivation. They also scored significantly higher on measures of state/trait anxiety, suggestibility, and fantasy proneness, though these did not explain the effects of group or condition. Regression analysis found hallucination proneness to be the best predictor of the increase in PLEs, with state anxiety also being a significant predictor. Fantasy proneness and suggestibility were not significant predictors. Conclusion. This study suggests the increase in PLEs reported during sensory deprivation reflects a genuine aberration in perceptual experience, as opposed to increased tendency to make false reports due to suggestibility of fantasy proneness. The study provides further support for the use of sensory deprivation as a safe and effective nonpharmacological model of psychosis.